Demand for Money in Mozambique : Was There a Structural Break? - Pinon-Farah, Marco (Washington, D.C. : International Monetary Fund, 1998)
The paper provides estimates of an error-correction model of the demand for narrow money (M1) and broad money (M2) in Mozambique. In addition, it assesses whether the rapid growth in money balances during 1996-97 represents a structural break or can be associated with the rapidly expanding economic activity and lower opportunity costs of holding money. In contrast with several studies of economies at a similar level of development as Mozambique, the paper obtains statistically significant coefficients for both financial and real explanatory variables. In this connection, it successfully includes the yield of foreign instruments (expressed in local currency) as one of the key explanatory variables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet